2019
DOI: 10.1001/jamanetworkopen.2019.6716
|View full text |Cite
|
Sign up to set email alerts
|

Processes of Care Associated With Risk of Mortality and Recurrent Stroke Among Patients With Transient Ischemic Attack and Nonsevere Ischemic Stroke

Abstract: Key Points Question Which processes of care are associated with reduced risk of mortality or recurrent stroke after transient ischemic attack or nonsevere ischemic stroke? Findings In this cohort study of 8076 patients with transient ischemic attack or nonsevere ischemic stroke, only 1216 (15.3%) received without-fail care, defined as receiving all guideline-concordant processes of care for which they were eligible (ie, brain imaging, carotid artery imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 35 publications
1
27
0
Order By: Relevance
“…Such comparative studies remain rare, even for developed countries. People with a history of stroke represent the group with the highest stroke risk, and studies have shown that recurrent stroke was not uncommon among stroke patients and could be fatal [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Such comparative studies remain rare, even for developed countries. People with a history of stroke represent the group with the highest stroke risk, and studies have shown that recurrent stroke was not uncommon among stroke patients and could be fatal [8] , [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Although a facility may be satisfied with an 88.0% pass rate on a consolidated measure of quality, at the patient-level, only 54.0% of patients at that facility received all of the care for which they were eligible. In a study 30 of patients with TIA and ischemic stroke, without-fail care was associated with 31.2% lower odds of 1-year mortality (adjusted OR, 0.69; 95% CI, 0.55-0.87), providing evidence to support the association between quality and outcome. Health care systems should consider including TIA in their existing stroke quality measurement programs and should consider evaluating progress against all-or-none quality measures.…”
Section: Discussionmentioning
confidence: 93%
“…The primary effectiveness outcome was the “without-fail” rate, defined as the proportion of Veterans with TIA who received all of the processes of care for which they were eligible from among seven processes of care: brain imaging, carotid artery imaging, neurology consultation, hypertension control, anticoagulation for atrial fibrillation, antithrombotics, and high/moderate potency statins [37]. These seven measures were included in the without-fail rate because they are both guideline-recommended processes of care and they have been associated with improvements in TIA patient outcomes [37]. The without-fail rate is sometimes also referred to as “defect-free” care [38, 39].…”
Section: Methodsmentioning
confidence: 99%